Macrophage Depletion Reduces Disease Pathology in Factor H-Dependent Immune Complex-Mediated Glomerulonephritis. (20th January 2022) - Jacob, Alexander; Phelps, Michael; Fraher, Shane; Lopez, Marcos; Chang, Anthony; Quigg, Richard J.; Alexander, Jessy J.
Abstract : Complement factor H (FH) is a key regulator of the alternative pathway of complement, in man and mouse. Earlier, our studies revealed that the absence of FH causes the C57BL6 mouse to become susceptible to chronic serum sickness (CSS) along with an increase in the renal infiltration of macrophages compared to controls. To understand if the increased recruitment of macrophages (M ϕ s) to the kidney was driving inflammation and propagating injury, we examined the effect of M ϕ depletion with clodronate in FH knockout mice with CSS. Eight-week-old FHKO mice were treated with apoferritin (4 mg/mouse) for 5 wks and with either vehicle (PBS) or clodronate (50 mg/kg ip, 3 times/wk for the last 3 weeks). The administration of clodronate decreased monocytes and M ϕ s in the kidneys by >80%. Kidney function assessed by BUN and albumin remained closer to normal on depletion of M ϕ s. Clodronate treatment prevented the alteration in cytokines, TNF α and IL-6, and increase in gene expression of connective tissue growth factor (CTGF), TGF β -1, matrix metalloproteinase-9 (MMP9), fibronectin, laminin, and collagen in FHKO mice with CSS (P < 0.05 ). Clodronate treatment led to relative protection from immune complex- (IC-) mediated disease pathology during CSS as assessed by the significantly reduced glomerular pathology (GN) and extracellular matrix. Our results suggest that complement activation is one of the mechanism that regulates the macrophage landscape and thereby fibrosis. The exact mechanism remains to be deciphered. In brief, our data shows that M ϕ s play a critical role in FH-dependent ICGN and M ϕ depletion reduces disease progression.